Analysis of merchant income and business sustainability of tourism sector Kerinci Regency, Indonesia - Adrian, Adrian Purwanto; Erni Achmad; Nurhayati (The Asian Journal of Professional & Business Studies, 2024)
This study aims to determine the socio-economic characteristics of traders in the tourism sector of Kerinci Regency, to analyze the factors that affect the income of traders in the tourism sector of kerinci regency and see the prospects for the sustainability of the tourism sector business in kerinci regency (case study of Kerinci Lake, Semurup Hot Water and smoky telun waterfall). The research method used is quantitative descriptive analysis with multiple linear regression analysis tools with processing using eviews and multidimensional scalling methods using rapfish analysis tools. The results showed that the influence of capital variables, working hours and length of business had a significant effect on the income of traders in the tourism sector of Kerinci district, but the labor variable had no significant effect on the income of traders in the tourism sector of Kerinci district. While the sustainability of the ecological dimension, economic dimension, social dimension, technological dimension and institutional dimension has a fairly sustainable sustainability index. In order for the value of this index in the future can be maintained and improved with a very sustainable status, it is necessary to improve the sensitive attributes that affect the value of ecological, economic, social, technological and institutional indices.